About Lyapunov characteristic indices - Nikitina, N. V. (Reports of the National Academy of Sciences of Ukraine, 2015)
An approach to finding the Lyapunov characteristic indices is presented for the tasks of chaotic motions. The approach is based on the analysis of the bifurcations of points of a trajectory.